Direct Participation of a Higher Education Institution Employees in the Organisational Change Process - a Study Report - Katarzyna Szelagowska-Rudzka (Institute of Economic Research (IER), 2017)
Changes in the organisation require its adjustment through the process of organisational change. For changes to bring expected, positive results, all employees should be involved. Employee direct participation is one of the most effective methods of winning them for change and leading them to positive reaction in form of cooperation, engagement and reduction of resistance. The objective of this study is to analyse the process of change of the organisational structure (number of departments) at a faculty of a Pomeranian university, in terms of direct participation of the research and teaching and the teaching staff in the process. The study involved direct polling. The study sample (the faculty and its employees) has been intentionally selected. The study revealed that the employees participate in the change cycle in a limited way, indifference and resistance being their main attitudes. The results suggest that causes of this state are the autocratic style of the change initiators, little time devoted to involve employees in the process, and the negative atmosphere caused by staff rotation (dominant internal factor).
Keywords: I23; M12; M54; 330; employee direct participation; organizational changes; higher education institutions; the cycle of organisational change process; employee resistance to change